Evaluation of Natural Technological Interfaces for Children with Psychomotor Disabilities - Beltramone, D. A. (2015)
Fil: Beltramone, D. A. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Ingeniería Biomédica; Argentina.